EFEKTIFITAS SENSORI INTEGRASI UNTUK MENINGKATKAN KEMAMPUAN MENULIS PERMULAAN PADA ANAK AUTIS DI TI-JI HOME SCHOOLING PADANG - Petrin - Kasdanel (Jurnal Penelitian Pendidikan Khusus, 2013)
This research background by the problems that researchers find in Home Schooling Padang Tiji, an autistic child who was eight years old, still has not been able to write the beginning, especially the vowels (a, i, u, e, o). This research Single Subject Research approach, the ABA design and data analysis techniques using visual analysis chart. Measurement variables using the percentage of each vowel can be written children properly. Observations made with the first three sessions, the session before being given intervention baseline (A1) performed seven times of observation, the percentage of vowels writing skills in this condition lies in the range of 0%, and 20% is at the confluence of unity, kadua third, fifth, sixth and seventh day the child can not be any writing beginning in vowels, but at a meeting of the four children to write a single vowel is the letter "i". Second, the intervention sessions (B) by using the Sensory Integration observations were made as much as ten times, the percentage of children beginning writing skills in this condition lies in the range of 20%, 40%, 60%, and 80% of children are able to write the vowels (a, i , u, o). Third session baseline (A2) is done five times of observation, the results obtained in the child's ability to write the beginning of the increase that is in the range of 90% which earlier children can write letters (a, i, u, o) to 100%. Based on these results it can be concluded Sensory Integration methods are effective in improving writing skills for children beginning at Autism Home Schooling Padang Tiji.